Analisis Kepuasan Penghuni Kost Mahasiswa Di Lingkungan Universitas Ngudi Waluyo Menggunakan Algoritma C4.5 - Ramadhan, Krisna Cahya; Sipayung, Yoannes Romando (Fakultas Ilmu Komputer Universitas Almuslim Bireuen - Aceh, 2023)
This study aims to measure student satisfaction with boarding houses or contracts. To achieve this goal, the authors implement the C4.5 algorithm in data analysis. Data on student satisfaction was taken through a survey covering various factors related to price, facilities, strategic layout, and the quality of the boarding house or contract. Algorithm C4.5 is used to produce a decision-making model based on criteria that are relevant to the level of student satisfaction. The results of this model provide valuable information in understanding what factors most influence student satisfaction with boarding houses or contracts. The results showed that the C4.5 algorithm was successful in building a model capable of classifying the level of student satisfaction with boarding houses or contracts with high accuracy. The results of this study are expected to help boarding or contract parties to increase student satisfaction. In addition, this research can also be a basis for further research in the field of student satisfaction and the application of the C4.5 algorithm to similar problems.